Landslide Susceptibility Assessment of a Railway Based on GIS Application - Wahyu Tamtomo Adi; Adya Aghastya; Rusman Prihatanto; Artanto Rizky Cahyono; Izza Anwer (Journal of Railway Transportation and Technology, 2023)
This study uses GIS-based maps to identify the potential for landslide movement on the railroad section between Prupuk Station and Purwokerto Station. The preparation was conducted by overlaying various maps obtained by online resource data, including rainfall, slope, geology, soil type, and land use, by using the DVMBG 2004 landslide prediction model. The distribution of landslide susceptibility levels shows that of the overall railway lines, 1.10% was very low, 17.29% was low, 63.16% was medium, 18.25% was high, and 0.21% was very high. The results of this study can be used as a reference for operators to provide information systems, landslide monitoring, and mitigation systems, especially for railroads in areas with high and very high vulnerability for landslides. Detailed conditions of landslide parameters and assessment of landslide occurrence on the location are needed to improve the accuracy of the models.